The barriers to interprofessional care for cancer cachexia among Japanese healthcare providers: A nationwide survey - Tateaki Naito; Hidetaka Wakabayashi; Sakiko Aso; Masaaki Konishi; Masakazu Saitoh; Vickie E. Baracos; Andrew J. Coats; Stefan D. Anker; Lawrence Sherman; Tatiana Klompenhouwer; Noriyasu Shirotani; Akio Inui; et al. (Wiley, 2024)
Abstract Background Cancer cachexia is a severe complication of advanced malignancy, with few therapeutic options. To promote interprofessional care for cancer cachexia, healthcare providers' needs should be addressed in detail. This pre‐planned subgroup analysis of the Global Educational Needs Evaluation: a systemic interprofessional study in cancer cachexia (GENESIS‐CC) survey aimed to identify barriers to interprofessional care of cancer cachexia in Japan. Methods A nationwide survey was electronically conducted for healthcare providers in oncological or general healthcare facilities from January to March 2021 in Japan. The Japanese Regional Advisory Board developed a barrier scoring system with 33 from the 58 original survey items to quantify six domains of barriers: (1) lack of confidence, (2) lack of knowledge, (3) barriers in personal practice, (4) barriers in perception, (5) barriers in team practice and (6) barriers in education. The largest possible barrier score was set at 100 points. We compared the scores by profession. Results A total of 1227 valid responses were obtained from 302 (24.6%) physicians, 252 (20.5%) pharmacists, 236 (19.2%) nurses, 218 (17.8%) dietitians, 193 (15.7%) rehabilitation therapists and 26 (2.0%) other professionals. Overall, 460 (37.5%) were not very or at all confident about cancer cachexia care, 791 (84.1%) agreed or strongly agreed that care was influenced by reimbursement availability and 774 (81.9%) did not have cancer cachexia as a mandatory curriculum. The largest mean barrier score (± standard deviation) was 63.7 ± 31.3 for education, followed by 55.6 ± 21.8 for team practice, 43.7 ± 32.5 for knowledge, 42.8 ± 17.7 for perception and 36.5 ± 16.7 for personal practice. There were statistically significant interprofessional differences in all domains (P < 0.05), especially for pharmacists and nurses with the highest or second highest scores in most domains. Conclusions There is a need to improve the educational system and team practices of cancer cachexia for most Japanese healthcare providers, especially pharmacists and nurses. Our study suggests the need to reform the mandatory educational curriculum and reimbursement system on cancer cachexia to promote interprofessional care for cancer cachexia in Japan.